A novel three-dimensional network-based stearic acid/graphitized carbon foam composite as high-performance shape-stabilized phase change material for thermal energy storage. (15th November 2021) - Wu, Renquan; Gao, Wei; Zhou, Yunhong; Wang, Zhuqi; Lin, Qilang
Abstract: Three-dimensional porous carbon materials have received extensive attention as supports for shape-stabilized phase change materials (PCMs). In order to improve the loading capacity, thermal conductivity and encapsulation performance for PCMs, a three-dimensional graphitized carbon foam (GCF) was developed with gradient hierarchical porous surface. The GCF was successfully prepared by pyrolysis of nano-magnesium oxide/epoxy resin mixture followed by surface treatment through a carbon-thermal reaction of Fe2 O3 . Using the GCF prepared at 1200 °C (GCF-1200) as a support for stearic acid (SA), a novel three-dimensional network-based SA/GCF composite was achieved as shape-stabilized PCM. The results show that the GCF-1200 has a large SA loading capacity of 84.66 wt% without any liquid leakage. The prepared SA/GCF-1200 composite exhibits a good interfacial bonding between the GCF-1200 and SA without obvious phase separation in its fracture surface. The composite possesses a high compressive strength of 9.45 MPa increasing by about 3.02-fold compared with the GCF-1200, and meanwhile has a significantly improved thermal conductivity of 1.012 W/m K by 4.36 times that of pristine SA. In addition, the melting and freezing enthalpy for the composite was measured as 181.8 and 182.7 J/g, respectively, which corresponds to a thermal storage efficiency of up to 99.9%. More importantly, it presents excellent thermal reliability and chemical stability without evident changes in enthalpy after 200 thermal cycles. Therefore, the composite has a great potential for thermal energy storage applications. Graphical abstract: Image 1 Highlights: Graphitized carbon foam (GCF) is obtained with gradient hierarchical porous surface. Large loading capacity and high thermal conductivity of the GCF is achieved. A good interfacial bonding between the GCF and stearic acid (SA) is observed. A three-dimensional network-based shape-stabilized SA/GCF composite is prepared. The composite phase change material has a good thermal stability and reliability.